The Seasonality of Labour in Ceramic Production and Agriculture in the Ancient Greek Rural World - Tomei, Francesca (Journal of Mediterranean Archaeology, 2024)
This article explores the seasonality of labour in ceramic production and its correlation with agricultural tasks, focusing on a Hellenistic kiln site in Sant’Angelo Vecchio, southern Italy, in the hinterland of Metaponto. Through a comprehensive examination of archaeological data and the outcomes of an experimental archaeology project, the study estimates the labour required for various stages of the pottery-making operational sequence. The findings reveal that small-scale rural workshops mainly produced limited quantities of items primarily for household and agrarian use. Only two or three individuals, working part-time, were needed to manage the various tasks involved, such as raw material collection, transportation, clay preparation, vessel shaping and kiln firing. The findings also demonstrate that the seasonal nature of their pottery work could be fitted within the seasonal rhythms of agricultural activities. This research highlights the interconnectedness of all productive activities in the region; sites and tasks are intricately linked, fostering a flexible and seasonal labour system in both ancient and modern Mediterranean societies.